ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH DALAM TERJEMAHAN DRAMA ‘AUDATUL FIRDAUS KARYA ALI AHMAD BAKATSIR (KONSERVATIF BUDAYA MELALUI KARYA SASTRA) - Malia Fransisca; Amin Suyitno; Endang Rochmiatun (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2023)
One element of culture is language and knowledge. This language is manifested in all aspects of life in spoken and written form. We use spoken language as a means of communication. We will find written language in literary works. Even though it is only in the form of sheets or books, literary works have contributed to the preservation of culture and important state moments. One of the literary works that played an important role during Indonesia's independence was the drama 'Audatul Firdaus' by Ali Ahmad Bakatsir. The researcher wants to reveal the drama 'Audatul Firdaus' by using Norman Fairclough's critical discourse analysis to get broad and deep results. In Norman Fairclough's critical discourse analysis, there are 3 elements, namely text, discourse practices and socio-cultural practices. So, Norman Fairclough's critical discourse analysis does not only dig up information from intrinsic elements, but also extrinsic ones. This research method is descriptive qualitative with a library research approach. As forthe results of this study, from the intrinsic elements, the setting of time, place and style of language used in writing the drama 'Audatul Firdaus' was found. From an extrinsic point of view, the drama 'Audatul Firdaus' was written to inform Arab and Egyptian citizens about the struggle of the heroes to gain the independence of the Unitary State of the Republic of Indonesia.